Skoolie! : how to convert a school bus or van into a tiny home or recreational vehicle - Sutherland, Will (Donald Will), 1984- (Storey Publishing, 2019)
"This complete guide to turning a school bus into a tiny house brings the dream of a nomadic life and a cozy home on wheels within reach -- and within budget -- featuring how-to photos along with creative layout ideas and profiles of skoolie fanatics."--Provided by publisher.